2016
DOI: 10.3389/fnhum.2016.00522
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar and Spinal Direct Current Stimulation in Children: Computational Modeling of the Induced Electric Field

Abstract: Recent studies have shown that the specific application of transcranial direct current stimulation (tDCS) over the cerebellum can modulate cerebellar activity. In parallel, transcutaneous spinal DC stimulation (tsDCS) was found to be able to modulate conduction along the spinal cord and spinal cord functions. Of particular interest is the possible use of these techniques in pediatric age, since many pathologies and injuries, which affect the cerebellar cortex as well as spinal cord circuits, are diffuse in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
4
39
0
Order By: Relevance
“…provided mechanistic foundation to these empirical findings (29)(30)(31)(32). It is then possible that tsDCS could also influence locomotor learning.…”
Section: Introductionmentioning
confidence: 87%
“…provided mechanistic foundation to these empirical findings (29)(30)(31)(32). It is then possible that tsDCS could also influence locomotor learning.…”
Section: Introductionmentioning
confidence: 87%
“…Models of SCS have been continuously refined and applied from the early 80's through recent efforts 1,2,5,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] (see Table 1). Development of models of increasing complexity offered mirrored general enhancements in numerical modeling techniques (finite element analysis), with proprietary efforts by numerous groups, each subject to multiple version iterations.…”
Section: Broad Impact Of An Open-source High-resolution Computationalmentioning
confidence: 99%
“…Parazzini and colleagues in 2014 and Fiocchi and colleagues in 2016 developed an MRIderived SCS model for non-invasive SCS with enhanced anatomical precision in vertebrae, CSF, and spinal cord; however, other major spinal canal tissue compartments, such as epidural space, dura mater, and roots were not modelled. Moreover, it was unclear whether epidural fat was included in the FEM model 20 . In 2013, Laird and colleagues developed a limited precision SCS model while modeling spinal root fiber as an electrical cable model 43 .…”
Section: Anatomical Details Of Prior Scs Modelsmentioning
confidence: 99%
“…Here, computational modeling studies have shown that the ctDCS electric field distribution reaches the human cerebellum where the posterior and the inferior parts of the cerebellum (i.e., lobules VI-VIII) are particularly susceptible (Grimaldi et al, 2016). However, a lobular atlas-based analysis of subject-specific electric field distribution during ctDCS was not found in the literature , , (Fiocchi et al, 2016). Therefore, the main objective of this technology report is to present a freely available computational pipeline that allows visualization of the lobular electric field distribution during ctDCS.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the goal is an optimal electrode placement, e.g., with more focal high-definition (HD) ctDCS montages (Fiocchi et al, 2017), that can in principle direct the electric field towards deeper targets by taking advantage of the high conductivity of the CSF and the interhemispheric fissure. Moreover, computational modeling , , (Fiocchi et al, 2016) is important to address the inter-subject variability in the ctDCS effects for its clinical translation (Ferrucci et al, 2016). This is crucial since ctDCS effects were recently said to be mediated by mechanisms other than cerebellar excitability changes (Grimaldi et al, 2016) since non-focal electric field with two-electrode montages may affect brain areas other than cerebellum.…”
Section: Introductionmentioning
confidence: 99%